On Unstable Ground: Trans-Civic, Trans Gender Fluidity in Chester’s ‘Play of the Flood’ - Redfern, Gillian (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2024)
This article explores potential audience reception of the character Uxor in the Chester ‘Play of the Flood’ in relation to the notion of gendered place in medieval Chester. After discussing the implications for divergent readings of Uxor according to cis-centric understandings of place of performance, I interrogate the possibilities of trans places and people in medieval Chester in order to trouble the historically cis approach to Uxor’s performance and potential reception. Ultimately, I posit that Uxor inhabits a trans identity that in a necessarily contingent and temporary way allows trans-Uxor to secure spiritual, if not physical, salvation for those denied access to the ark.